Analysis of the MHC class II encoded components of the HLA class I antigen processing pathway in ankylosing spondylitis. Issue 1 (January 1994) - Burney, R O; Pile, K D; Gibson, K; Calin, A; Kennedy, L G; Sinnott, P J; Powis, S H; Wordsworth, B P
Abstract : OBJECTIVES--The evaluation of the role of polymorphism within the class II encoded antigen processing genes, LMP2 and TAP, in susceptibility to ankylosing spondylitis (AS). METHODS--Eighty five patients with ankylosing spondylitis, 35 B27 positive healthy controls, and 55 unrelated healthy controls were studied. TAP1 and TAP2 alleles were assigned by ARMS PCR, and LMP2 alleles were assigned by restriction enzyme digestion of a PCR product. RESULTS--The TAP1C allele was increased in the AS group (6%) compared with random controls (1%), p = 0.03 and TAP2E was increased in AS (3.5%) compared with random controls (0%), p = 0.05. However, the frequencies of these alleles were also increased in B27 matched controls. There were no differences in LMP2 allele or genotype frequencies between AS and either of the control groups. Partitioning of patients according to presence or absence of uveitis did not reveal any significant associations. CONCLUSIONS--Increases of the minor TAP alleles, 1C and 2E, in AS reflect linkage disequilibrium between these alleles and HLA-B27. Polymorphism of the class I antigen processing pathway does not contribute significantly to AS susceptibility nor to the development of anterior uveitis associated with AS.